Testing the environment Kuznets curve (EKC) hypothesis in the Democratic Republic of Congo - Bwami Kahombera RUPIN; Neema Mpumu ESTHER; Muzee Kazamwali LÉON; Furaha Mirindi GERMAINE (Present Environment and Sustainable Development)
This paper investigates the interplay between economic growth and environmental degradation in the Democratic Republic of Congo (DRC) from 1990 to 2020. Despite extensive research on the environmental Kuznets curve (EKC), the applicability of this hypothesis remains non-generalisable, influenced by various factors such as the level of economic development, research methodologies, and researchers' understanding of the topic. Utilising the Phillips-Perron (PP) and Zivot-Andrews (ZA) unit root tests for stationarity, and Pesaran's cointegration test for long-term dynamics, this study applied the ARDL (Autoregressive Distributed Lag) model to series integrated of order I(0) and I(1). Findings confirm the presence of the EKC and a unidirectional causal relationship between GDP and CO2 emissions in the DRC. These results highlight the significance of wealth creation for sustainable development in the country.